Strategi Sistem Operasional Pelayanan Berbasis SWOT Untuk Meningkatkan Penerimaan Pajak Kendaraan Bermotor Di Unit Pelayanan Teknis Medan Utara Badan Pengelolaan Pajak Dan Retribusi Daerah Provinsi Sumatera Utara - Jufrijal; David Suriadi Marpaung; Abu Bakar Gentie Raya; Sofian; Ernawati; Nilawati Nasti; Supriadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The formulation of the problem in this study is: How is the SWOT-based Operational System Strategy to Increase Motor Vehicle Tax Revenue. This study aims to determine the SWOT-based Operational System Strategy to Increase Motor Vehicle Tax Revenue. The results showed that; The UPT of the North Medan Regional Revenue Agency is in the quadrant I position, namely at the coordinates (0.45 and 0.7), where the appropriate alternative strategy in increasing local tax revenue is using the SO strategy, which is to use all strengths to take advantage of the opportunities they have. Covers; Utilizing advances in communication and information technology in tax revenue; Increase cooperation with other institutions; Optimizing revenue with measurable Intensification and Extensification; Improving the quality of Apparatus Resources.